Prospective cohort studies of association between family history of liver cancer and risk of liver cancer. Issue 7 (7th March 2014) - Yang, Yang; Wu, Qi‐Jun; Xie, Li; Chow, Wong‐Ho; Rothman, Nat; Li, Hong‐Lan; Gao, Yu‐Tang; Zheng, Wei; Shu, Xiao‐Ou; Xiang, Yong‐Bing
Abstract : Uncertainty remains on the relationship between a family history of liver cancer and liver cancer risk in prospective cohort studies in a general population. Thus, we examined this association in 133, 014 participants in the Shanghai Women's and Men's Health Studies. Family history of liver cancer was categorized through dichotomous and proportional score approaches. Hazard ratios (HRs) and 95% confidence intervals (CIs) were derived using the Cox proportional hazards models with adjustment for potential confounders. A meta‐analysis of observational studies through December 2013 on liver cancer risk in relation to family history of liver cancer was also performed. Study‐specific risk estimates were combined using fixed or random effects models depending on whether significant heterogeneity was detected. For the Shanghai Women's and Men's Health Studies, 299 liver cancer cases were identified during follow‐up through 2010. Family history of liver cancer was associated with liver cancer risk using both binary indicator (HR = 2.60, 95% CI: 1.77–3.80) and proportional score (high‐risk vs . minimal‐risk category: HR = 3.03, 95% CI: 1.73–5.31), with increasing HRs for increasing score categories. The meta‐analysis also showed an increased risk for those with a family history of liver cancer (relative risk = 2.55, 95% CI: 2.05–3.16). Family history of liver cancer was related to increased risk of liver cancer in Chinese population. This risk is particularly high for those with an affected mother. The "dose‐response" of risk with an increasing family history score of liver cancer might further facilitate future cancer prevention programs on identifying individuals with the highest potential liver cancer risk. Abstract : What's New? Heritable factors likely contribute to a person's risk of developing liver cancer, but whether a family history of the disease increases that risk remains unclear. Here, in two prospective cohorts derived from the Shanghai Women's and Men's Health Studies, an association between family history of liver cancer and increased risk of liver cancer was detected in the general Chinese population. A "dose‐response" risk was identified, in which risk increased in tandem with an increased family history score of liver cancer, potentially allowing minimal‐, intermediate‐, and high‐risk individuals to be distinguished in a liver cancer prevention program.